2018
DOI: 10.1016/j.ijid.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Xpert MTB/RIF assay for the diagnosis of smear-negative pulmonary and extrapulmonary tuberculosis in Madagascar

Abstract: The implementation of a rapid diagnosis programme for TB in a resource-poor setting is feasible. The performance of the Xpert-MTB/RIF was remarkable in this difficult-to-diagnose population. HIV prevalence in this study was much higher than the prevalence reported in the general population in Madagascar, in patients with TB and patients with conditions other than TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
(18 reference statements)
4
7
2
Order By: Relevance
“…Because of the lack of rapid and accurate methods, the diagnosis of smear-negative TB cases remains a challenge in the world. Our results were in line with previous clinical studies ( [14][15][16][17], suggesting the use of the Xpert assay for the improvement of the detection of smear-negative cases, especially in regions without access to equipped laboratory infrastructures.…”
Section: Discussionsupporting
confidence: 91%
“…Because of the lack of rapid and accurate methods, the diagnosis of smear-negative TB cases remains a challenge in the world. Our results were in line with previous clinical studies ( [14][15][16][17], suggesting the use of the Xpert assay for the improvement of the detection of smear-negative cases, especially in regions without access to equipped laboratory infrastructures.…”
Section: Discussionsupporting
confidence: 91%
“…If not, the microbiology would have reported a prevalence of 22.5%. similar to the TB prevalence reported by Rakotoarivelo et al (30) who obtained a global prevalence of 32.8%, 31.7% with culture and 31.8% with GeneXpert 31.8%. However, Madagascar it considered as a high TB prevalent country while Mexico is considered as a medium TB prevalent country.…”
Section: Discussionsupporting
confidence: 89%
“…However, due to the fact that within our population there was a subgroup with samples showed by BAL as well as by TLCB; the samples were analyzed simultaneously by culture and by GeneXpert ® MTB/RIF sample. This analysis revealed the same TB real prevalence through BAL than by TLCB, but a higher calculated prevalence by TLCB than by BAL (non-significant P value); none of our patients with positive GeneXpert had a negative culture, unlike other authors that had a negative result in culture and positive in GeneXpert (1,18,30). In the same vein, it was observed that within the HIV population the real TB prevalence was the same by BAL than by TLCB, while the TB calculated prevalence was greater in TLCB than in BAL (non-significant P value).…”
Section: Discussionsupporting
confidence: 58%
“…C reactive protein (CRP) is a marker of inflammation and carries high sensitivity for screening active PTB [5]. The Xpert mycobacterium tuberculosis/rifampicin (Xpert MTB/RIF) is a World Health Organization (WHO) approved test for the detection of tuberculosis as well as rifampicin resistance and carries high sensitivity and specificity for diagnosing pulmonary and extra-PTB [6]. It also has a high sensitivity in diagnosing PTB in children [7].…”
Section: Introductionmentioning
confidence: 99%